2020
DOI: 10.4067/s0034-98872020000500573
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiología del cáncer de tiroides en un Instituto Oncológico. Efecto de las nuevas recomendaciones clínicas

Abstract: Incidence of thyroid cancer in an oncological clinic of Santiago, Chile Background: In Chile, Thyroid cancer (TC) is included in a list of diseases that have a guaranteed access to treatment, endorsed by the Ministry of Health. The care burden of the disease will depend on its incidence. Aim: To estimate the incidence of TC in Chilean patients with access to thyroid surgery and describe its histopathological characteristics. Material and methods: Analysis of the registry of all thyroidectomies performed at a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thus, as the recognition of nuclear alterations in PTC increased, the incidence of FTC decreased, with PTC currently being the most frequently diagnosed thyroid cancer ( 4 6 ). Chilean studies have found a similar situation, where 91.8%-96.3% of the thyroid cancers are PTC and only 2.4%-5.1% are FTC ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 69%
“…Thus, as the recognition of nuclear alterations in PTC increased, the incidence of FTC decreased, with PTC currently being the most frequently diagnosed thyroid cancer ( 4 6 ). Chilean studies have found a similar situation, where 91.8%-96.3% of the thyroid cancers are PTC and only 2.4%-5.1% are FTC ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 69%
“…The following four criteria were required for each study: (1) the study design must be a clinical cohort study or diagnostic test; (2) the study must relate to the accuracy of S-Detect for the PLOS ONE differential diagnosis of benign and malignant thyroid nodules,and the final assessments from S-Detect were in dichotomized form: possibly benign and possibly malignant; (3) all thyroid nodules were histologically confirmed; and(4) published data in the fourfold (2×2) tables must be sufficient. If the study did not meet all the inclusion criteria, it was excluded.…”
Section: Selection Criteriamentioning
confidence: 99%
“…The QUADAS criteria include 14 assessment items. Each item was scored as "yes" (2), "no" (0), or "unclear" (1). The QUADAS score ranged from 0 to 28, and a score � 22 indicated good quality.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…De hecho, el cáncer de tiroides es uno de los tipos de neoplasias que ha aumentado en los últimos ocho años (Veronica, 2018). En Manabí el cáncer de tiroides tanto en hombres como en mujeres ocupa el segundo lugar a nivel nacional después de Pichincha, seguido por Azuay, Guayaquil y Loja, según registros existentes en SOLCA (Sapunar Z & Ferrer-Rosende, 2020). Los factores de riesgo que se asocian con el cáncer de tiroides, además de la exposición a radiación, la obesidad, el sedentarismo, la diabetes mellitus tipo II, contaminantes químicos como bisfenol A, cadmio, la baja ingesta de yodo, la ingesta excesiva de nitritos y factores reproductivos en la mujer (Sapunar Z & Ferrer-Rosende, 2020).…”
Section: Introductionunclassified